1999
DOI: 10.1103/physrevc.60.064614
|View full text |Cite
|
Sign up to set email alerts
|

Reaction rates for neutron capture reactions to C, N, and O isotopes to the neutron rich side of stability

Abstract: The reaction rates of neutron capture reactions on light nuclei are important for reliably simulating nucleosynthesis in a variety of stellar scenarios.Neutron capture reaction rates on neutron-rich C-, N-, and O-isotopes are calculated in the framework of a hybrid compound and direct capture model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 44 publications
10
38
0
Order By: Relevance
“…Fig. 6 shows that the results of the AMS measurement at 25 keV are in fair agreement with the previous experimental [51,52] and theoretical [50] data, but about two times higher than the JEFF-3.1 evaluation. For the two higher neutron energies a striking discrepancy was found with respect to the strength of the 143 keV resonance, which turned out to be a factor of 10 lower than the calculation of Herndl et al [50] (indicated by the horizontal bars in Fig.…”
Section: C: a Potential Neutron Poisonsupporting
confidence: 79%
See 3 more Smart Citations
“…Fig. 6 shows that the results of the AMS measurement at 25 keV are in fair agreement with the previous experimental [51,52] and theoretical [50] data, but about two times higher than the JEFF-3.1 evaluation. For the two higher neutron energies a striking discrepancy was found with respect to the strength of the 143 keV resonance, which turned out to be a factor of 10 lower than the calculation of Herndl et al [50] (indicated by the horizontal bars in Fig.…”
Section: C: a Potential Neutron Poisonsupporting
confidence: 79%
“…At temperatures above T 8 = 3 the reaction rate is dominated by the 143 keV resonance, at lower temperatures by the p-wave and s-wave contributions. The calculations [50] are in reasonable agreement with two previous experiments [51,52], but exhibit a significant discrepancy compared to the most recent evaluation of JEFF-3.1, which is consistently higher than the calculation, culminating in a 25 times higher peak value for the 143 keV resonance.…”
Section: C: a Potential Neutron Poisonsupporting
confidence: 73%
See 2 more Smart Citations
“…Previous experimental data and a comparison with calculation for 13 C(n,g) 14 C (Herndl et al 1999) indicate that the total capture cross section is dominated by a p-wave resonant contribution at energies above 20 keV. The non-resonant contribution is considerably lower and agrees well with the value extrapolated by the 1/v law from the thermal cross section (Herndl et al 1999). At temperatures above 0.3 GK the reaction rate is dominated by the 143 keV resonance, at lower temperatures p-wave and s-wave contributions are dominant.…”
Section: C(ng) 14 Csupporting
confidence: 73%